Exploring the phenotypic consequences of tissue specific gene expression variation inferred from GWAS summary statistics - Alvaro N. Barbeira (Nature Portfolio, 2018)
Phenotypic variation and diseases are influenced by factors such as genetic variants and gene expression. Here, Barbeira et al. develop S-PrediXcan to compute PrediXcan results using summary data, and investigate the effects of gene expression variation on human phenotypes in 44 GTEx tissues and >100 phenotypes.